2018
DOI: 10.1038/s41467-017-02777-6
|View full text |Cite
|
Sign up to set email alerts
|

Combined chemical genetics and data-driven bioinformatics approach identifies receptor tyrosine kinase inhibitors as host-directed antimicrobials

Abstract: Antibiotic resistance poses rapidly increasing global problems in combatting multidrug-resistant (MDR) infectious diseases like MDR tuberculosis, prompting for novel approaches including host-directed therapies (HDT). Intracellular pathogens like Salmonellae and Mycobacterium tuberculosis (Mtb) exploit host pathways to survive. Only very few HDT compounds targeting host pathways are currently known. In a library of pharmacologically active compounds (LOPAC)-based drug-repurposing screen, we identify multiple c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
83
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 47 publications
(84 citation statements)
references
References 79 publications
1
83
0
Order By: Relevance
“…Mtb [DsRed-expressing H37Rv (24)] was cultured in Difco Middlebrook 7H9 broth (Becton Dickinson, Breda, The Netherlands) supplemented with 10% ADC (Becton Dickinson) and 0.05% Tween 80 (Sigma-Aldrich). One day before infection, Mtb cultures were diluted to a density corresponding with early log-phase growth (OD 600 of 0.25).…”
Section: Mtb Infection Of Macrophagesmentioning
confidence: 99%
“…Mtb [DsRed-expressing H37Rv (24)] was cultured in Difco Middlebrook 7H9 broth (Becton Dickinson, Breda, The Netherlands) supplemented with 10% ADC (Becton Dickinson) and 0.05% Tween 80 (Sigma-Aldrich). One day before infection, Mtb cultures were diluted to a density corresponding with early log-phase growth (OD 600 of 0.25).…”
Section: Mtb Infection Of Macrophagesmentioning
confidence: 99%
“…PDE (phosphodiesterase) inhibitors improve the clearance of Mtb in rabbit lungs, restrict Mtb growth, and increase mouse survival (Maiga et al, 2012; Subbian et al, 2011). Repression of CHUK (conserved helix-loop-helix ubiquitous kinase), identified by a human kinome siRNA screen, decreases intracellular Mtb load (Korbee et al, 2018). Inhibition of p38 MAPK (mitogen activated protein kinase) can restrict Mtb growth in murine macrophages (Stanley et al, 2014).…”
Section: Resultsmentioning
confidence: 99%
“…To dissect cellular responses to mycobacterial infection, we conducted both genome-wide and focused secondary CRISPR loss-of-function and CRISPRi screens. Unlike other kinds of host genetic screens (Korbee et al, 2018; Kumar et al, 2010; Li et al, 2016; Philips et al, 2005), our high-throughput CRISPR screens require host cell survival and, therefore, directly reveal processes targeted by intracellular mycobacteria in live host cells.…”
Section: Discussionmentioning
confidence: 99%
“…In our future studies we will be interested in genes that play a role at the interface of immune response and metabolism for which knock out mutants are available such as genes in toll-like receptor, leptin 43 and glucocorticoid receptor 44 signalling pathways. These studies could not only help elucidating the observed changes in metabolism during infection, but could also lead to the development of new medicines for treatment of TB or wasting syndrome using innovative host-directed therapeutic approaches 45 .…”
Section: Discussionmentioning
confidence: 99%